Perfil eletroforético das proteínas do plasma seminal de reprodutores taurinos e zebuínos de alta congelabilidade do sêmen - Oberst, Eneder Rosana (2001)
Two dimensional polyacrylamide gel electrophoresis (O’Farrel et al.,1977, modified by Rodnight et al., 1988), was performed in seminal plasma of Bos taurus taurus and Bos taurus indicus bulls from an IA Center. All the bulls were considered to have a semen with high freezeability. In a 15% polyacrylamide gels, stained with Commassie Blue, a total of 11 protein bands (10-24 kDa) was analyzed by their optical densities. In Bos taurus, the bands 13 (14-15 kDa) and 19 (16-18 kDa) were present in 28.6% of the seminal plasma samples examined. The remainder bands were present in all samples examined. No statistical significance was found between Bos taurus bulls samples in the bands 3 (15-16 kDa); 5 (16-17 kDa), 7 (11-12 kDa) and 9 (14-15 kDa). On the other hand, in Bos indicus it was found that the bands 11 (13-14 kDa), 19 and 23 (20-22 kDa) were present on 71% of the samples, the band 13 in 57% and the remainder were present in all samples. The band 15 (11-12 kDa) was the only one that did not show any variation between the Bos indicus bulls samples. Finally, five bands showed up differences (P<0,05) on their optical densities between species. In Bos taurus the bands with high optical densities were the 7 and 23 and in Bos indicus the bands with high optical densities were the 5, 15 and 21. The bands 7 and 23 were identified as aSFP and clusterin, by protein sequence. In a 8% polyacrylamide gels, three bands of 195; 66 and 55 kDa, present in 100% of the samples in both species, were analyzed. In Bos taurus samples, the opticals densities of 55 kDa band, imunoidentified as osteopontin were superior(P<0,05) than Bos indicus samples. The 66 kDa band was imunoidentified as albumin. In the Bos taurus samples, the bands did not show any variation between the bull samples, but in Bos indicus, the albumin optical densities showed significant variation between samples.